Ensuring Parameter Estimation Accuracy in 3PL IRT Modeling: The Role of Test Length and Sample Size - Hasan Djidu; Heri Retnawati; Haryanto Haryanto (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2023)
The objective of this simulation study was to evaluate the accuracy of item parameters estimation when employing the 3PL IRT model, mainly focusing on sample size and the length of the test (number of test items). The investigation used six datasets produced by WinGen, each comprising 5000 responses and varying test lengths within 10 to 40 items. For each dataset, the study conducted simulations and re-analyzed the data 15 times, generating a total of 2025 data subsets and estimating 225 parameters for each item. The results revealed that smaller sample sizes led to more pronounced biases, emphasizing a recommended minimum sample size of 3000 for precise parameter estimation. Additionally, the study found that a limited number of items (short test) yielded biased estimations and proposed a minimum of 25 or 40 test items for accurate estimation using the 3PL IRT model. These findings offer valuable insights for test developers in making informed decisions regarding sample sizes and test length, ultimately ensuring reliable and accurate parameter estimates.